Gold Nanoparticles Enhance the Tumor Growth-Suppressing Effects of Cetuximab and Radiotherapy in Head and Neck Cancer In Vitro and In Vivo - Sato, Takumi; Kakei, Yasumasa; Hasegawa, Takumi; Kashin, Masahiko; Teraoka, Shun; Yamaguchi, Akinobu; Sasaki, Ryohei; Akashi, Masaya (Cancers, 2023)
Introduction: Head and neck squamous cell carcinoma (HNSCC) treatment includes surgery, radiotherapy, and immunotherapy with the aim of eradicating cancer cells without affecting normal tissues. HNSCC expresses epidermal growth factor receptor (EGFR) and cetuximab, an IgG1 monoclonal antibody targeting epidermal growth factor receptor, has been approved for the treatment of HNSCC. However, cetuximab has low reactivity and induces serious side effects. Gold nanoparticles (AuNPs) were reported to enhance the local antitumor effects of radiotherapy without damaging normal cells. Methods and Results: This study investigated the in vitro effects of single and combination therapy with AuNPs (1.0 nM), cetuximab (30 nM), and radiotherapy (4 Gy) on a human HNSCC cell line, HSC-3. Combination treatment of AuNPs + cetuximab + radiotherapy markedly reduced HSC-3 numbers and proliferation and enhanced apoptosis compared with single and double combination treatments. Furthermore, the in vivo combination treatment (AuNPs + cetuximab + radiotherapy) of a xenograft model of HSC-3 cells transplanted into nude mice (BALB/cAJcl-nu/nu) reduced the tumor volume compared with the controls. Scanning electron microscopy demonstrated the presence of AuNPs in tumor tissues and toxicity analysis indicated that AuNPs had no toxic effect on normal tissues. Conclusions: This study showed that AuNPs alone do not have a tumor-suppressing effect, but they sensitize tumors to radiotherapy and bind to cetuximab, leading to enhanced antitumor effects.